Mutant p53R211* ameliorates inflammatory arthritis in AIA rats via inhibition of TBK1-IRF3 innate immune response - Yaling Zeng; Jerome P. L. Ng; Linna Wang; Xiongfei Xu; Betty Yuen Kwan Law; Guobing Chen; Hang Hong Lo; Lijun Yang; Jiujie Yang; Lei Zhang; Liqun Qu; Xiaoyun Yun; et al. (Inflammation Research, 2023)
Background Rheumatoid arthritis (RA) is an autoimmune inflammation disease characterized by imbalance of immune homeostasis. p53 mutants are commonly described as the guardian of cancer cells by conferring them drug-resistance and immune evasion. Importantly, p53 mutations have also been identified in RA patients, and this prompts the investigation of its role in RA pathogenesis. Methods The cytotoxicity of disease-modifying anti-rheumatic drugs (DMARDs) against p53 wild-type (WT)/mutant -transfected RA fibroblast-like synoviocytes (RAFLSs) was evaluated by MTT assay. Adeno-associated virus (AAV) was employed to establish p53 WT/R211* adjuvant-induced arthritis (AIA) rat model. The arthritic condition of rats was assessed by various parameters such as micro-CT analysis. Knee joint samples were isolated for total RNA sequencing analysis. The expressions of cytokines and immune-related genes were examined by qPCR, ELISA assay and immunofluorescence. The mechanistic pathway was determined by immunoprecipitation and Western blotting in vitro and in vivo. Results Among p53 mutants, p53 R213* exhibited remarkable DMARD-resistance in RAFLSs. However, AAV-induced p53 R211* overexpression ameliorated inflammatory arthritis in AIA rats without Methotrexate (MTX)-resistance, and our results discovered the immunomodulatory effect of p53 R211* via suppression of T-cell activation and T helper 17 cell (Th17) infiltration in rat joint, and finally downregulated expressions of pro-inflammatory cytokines. Total RNA sequencing analysis identified the correlation of p53 R211* with immune-related pathways. Further mechanistic studies revealed that p53 R213*/R211* instead of wild-type p53 interacted with TANK-binding kinase 1 (TBK1) and suppressed the innate immune TBK1–Interferon regulatory factor 3 (IRF3)–Stimulator of interferon genes (STING) cascade. Conclusions This study unravels the role of p53 R213* mutant in RA pathogenesis, and identifies TBK1 as a potential anti-inflammatory target.